The long term X-ray time lags of NGC 4051. Issue 1 (17th February 2019) - Papadakis, I E; Rigas, A; Markowitz, A; McHardy, I M
Abstract: We present the long term, frequency-dependent, X-ray time lags of the Seyfert galaxy NGC 4051. We used Rossi X-ray Timing Explorer ( RXTE ) light curves in the 2–4, 4–7, and 7–10 keV bands and we measured the time lags at 10 −7 –10 −6 Hz. This is the lowest frequency range that active galactic nuclei time lags have ever been measured. The variations in the higher energy bands are delayed with respect to the variations we observe at 2–4 keV, in agreement with the time lags at high frequencies. When we combine our results with those from the model fitting of the time lags at higher frequencies we find that that the X-ray hard lags in NGC 4051 follow a power law of slope ∼−1 over a broad frequency range, from ∼10 −7 to ∼10 −3 Hz. This is consistent with the time lags of Cyg X–1, a result which further supports the analogy between active galaxies and Galactic X-ray black hole binaries.